Proceedings of the Fifth Prasasti International Seminar on Linguistics (PRASASTI 2019) 2019
DOI: 10.2991/prasasti-19.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

Will Ideology Compete or Unite? Form and Function of Linguistic Landscape of Public and Private School in Malang City, East Java

Abstract: The presence or absence of a language in public space represents the strength or weakness of social group along with their ideology. School is the basis on which ideology is constructed through education. The use of language in school nameplate plays a role in the construction of ideology which leaves big problems, namely the occurrence of attraction between school branding, the social existence of both ethnic and religious, and language regulations that are obeyed and violated. Linguistic Landscape is a study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…The authors concluded, 'language plays an important role in forming a positive image' (Sumarlam et al, 2020a(Sumarlam et al, : 2624. In another study in the same city (Sumarlam et al, 2020b), a similar pattern was found for the use of languages on signs of halal food stalls and restaurants (n = 503). Monolingualism in Indonesian predominates (52%), followed by English (31%) and Javanese (8%); other languages such as Chinese, Japanese, Arabic and Dutch were found here and there.…”
Section: China and Indonesiasupporting
confidence: 68%
“…The authors concluded, 'language plays an important role in forming a positive image' (Sumarlam et al, 2020a(Sumarlam et al, : 2624. In another study in the same city (Sumarlam et al, 2020b), a similar pattern was found for the use of languages on signs of halal food stalls and restaurants (n = 503). Monolingualism in Indonesian predominates (52%), followed by English (31%) and Javanese (8%); other languages such as Chinese, Japanese, Arabic and Dutch were found here and there.…”
Section: China and Indonesiasupporting
confidence: 68%
“…LL research publications in Malaysia (Coluzzi & Kitade, 2015), Mecca, Saudi Arabia (Alsaif & Starks, 2019), and Nigeria (Inya, 2019). Some LL studies in Indonesia have also been carried out, Malang (Yannuar & Tabiati, 2016), (Sumarlam, 2020), (Sumarlam et al, 2019), (Purnanto & Ardhian, 2020), Gresik (Oktaviani, 2019), Yogyakarta (Andriyanti, 2019) (Erikha, 2018), Dili, Timor Leste (Taylor-Leech, 2012. No research in Indonesia has yet reported on the worship sign.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some LL researchers have reported the results of studies, such as [4], [5] [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [5], and [17]. LL research was also held in Indonesia, including [18] [19], [20], [21], [22], [23].…”
Section: Linguistic Landscapementioning
confidence: 99%